O movimento da Educação do Campo, as tensões na luta por um direito social e os sinais da construção de políticas públicas - Maria Antônia de Souza (EccoS – Revista Científica)
This article questions the rural education and intends to demonstrate signs of public policies construction which has been possible due to the effective rural workers participation. Current rural education has been effectively executed for a decade, taking the National Conference for a Rural Basic Education in 1998 as a landmark. It integrates the workers struggle for the accomplishment of a social right - education. It also takes for granted the concept of emancipatory education, in terms of Mészàros, putted against the concept of excludent education that ignores the rurality of Brazilian territory. Current rural education is opposed to the previous model. It is constructed collectively by workers, and in an increasing national movement it has been enhancing educational projects, partnerships, governmental segments engagement as well as the need of curricular changes, especially in higher education.